Language Learning Under Varied Conditions: Neural Indices of Speech Perception in Bilingual Turkish-German Children and in Monolingual Children With Developmental Language Disorder (DLD) - Rinker, Tanja; Yu, Yan H.; Wagner, Monica; Shafer, Valerie L. (Frontiers in Human Neuroscience, 2022)
Lateral temporal measures of the auditory evoked potential (AEP) including the T-complex (positive Ta and negative Tb), as well as an earlier negative peak (Na) index maturation of auditory/speech processing. Previous studies have shown that these measures distinguish neural processing in children with typical language development (TD) from those with disorders, and monolingual from bilingual children. In this study, bilingual children with Turkish as L1 and German as L2, were compared with monolingual German speaking children with developmental language disorder (DLD), and monolingual German speaking children with TD in order to disentangle effects of limited language input versus reduced perceptual abilities in the processing of speech and non-speech stimuli. Sensory processing reflected by the T-complex (or from lateral temporal electrode sites) was compared in response to a German vowel and a sine-wave tone in the three groups of children, ages 5 through 6 years. Stimuli were presented while children watched a muted video.Event-related potentials (ERPs) were time-locked to the vowels and tones. ERPs to the frequent (standard) stimulus within an oddball paradigm were analyzed at the left (T7) and right (T8) temporal electrode sites. The results revealed language status (monolingual, bilingual and DLD), stimulus (vowel and tone), and language test measures (receptive and expressive) all influenced the T-complex amplitudes. Particularly, the peak amplitude of Ta was modulated by language status and stimulus type. Bilingual children had significantly more negative Ta responses than the monolingual children with TD for both vowels and tones while DLD children differed from TD children only for the vowel stimulus. The amplitude of the T-complex was overall more negative at the left than at the right site. The Na peak latency was longer for the bilingual group than that observed for the two monolingual groups. The Tb latency was shorter for DLD and bilingual groups than that for TD children in the vowel condition, but no such latency difference between DLD and bilingual children was found. We suggest that the attenuated T-complex for the bilingual children indicates continued plasticity of auditory cortex to allow for learning of novel, second-language speech sounds.